Carbon-dioxide gas sensor using co-doped graphene nanoribbon: A first principle DFT study. (2021) - Deji,; Kaur, Navjot; Choudhary, B.C.; Sharma, Ramesh K.
Abstract: First Principle calculations along with non equilibrium Green's Function (NEGF) have been performed to sense CO2 gas molecule using armchair graphene nanoribbon (ArGNR) and its co-doped system. CO2 is one of the toxic gas produced from various sources. The development of more efficient gas sensor for detection of CO2 gas is required. Different sensing nanomaterials are optimized viz pristine ArGNR (Pr-ArGNR) and ArGNR co-doped with Boron-Phosphorus (BP-ArGNR), Boron–Nitrogen (BN-ArGNR), Boron–Arsenic (BAs-ArGNR) & Boron– Antimony (BSb-ArGNR). The transfer of charge between CO2 and these variants is analyzed in terms of adsorption energy, band structures and density of states (DOS). Computational Results show that Pr-ArGNR is not much sensitive to CO2 gas molecule in comparison to other variants. Whereas BP-ArGNR shows adsorption energy of −1.19 eV which is nearly eight times greater than Pr-ArGNR and BN-ArGNR. Large band gap variations are observed for BP-ArGNR from 1.91 eV to 1.56 eV. The DOS study confirms the interaction of CO2 molecule with different sensing materials used in our work. Significant changes are observed in density of states of BP-ArGNR. Therefore it is concluded that BP-ArGNR can be a promising sensing material for detection of CO2 gas.